The Role of Spiritual Blessing Energy Treatment in Optimizing Radish (Raphanus sativus L.). Growth and Crop Yield - Dahryn Trivedi; Vivek Dattaram Kadam; Tejas Bapu Gaikwad; Nikhil Rajendra Phutankar; Sambhu Mondal; Snehasis Jana (Journal of Precision Agriculture, 2026)
Background Enhancing crop productivity while minimizing chemical inputs remains a core objective of sustainable agriculture. This study investigated the efficacy of spiritual blessing energy treatments as a non-invasive biostimulant to optimize the growth dynamics and crop yield of radish (Raphanus sativus L.). Methods Seeds and land were exposed to Spiritual Blessing Energy Treatment (SBET) in her physical presence for about 4 minutes once, alongside untreated controls under identical environmental conditions. Morphological parameters and final biomass production were systematically evaluated. Results Photosynthesis traits such as number of leaves per plant, leaf width, and fresh weight of leaves per plant were significantly increased by 28.41% (p = 0.003), 45.81% (p ≤ 0.001), and 28.86% (p ≤ 0.001), respectively, in the blessing/biofield energy-treated radish group (BTRSG) compared to the control radish group (CONRSG). Moreover, root length, root width/girth, and root weight per plant were significantly increased by 39.68% (p ≤ 0.001), 32.13% (p ≤ 0.001), and 30.73% (p ≤ 0.001), respectively, in the BTRSG compared to the CONRSG. Besides, root yield (tons per hectare) was increased by 46.29% in BTRSG compared to the CONRSG. Conclusion These findings suggest that the spiritual blessing energy treatments (Trivedi Effect®) act as a powerful biostimulatory agent capable of optimizing plant ontogeny and radish yield and offering a sustainable paradigm for precision agronomy.
Keywords: radish